2013
DOI: 10.1155/2013/123847
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Spondylolisthesis Is Associated with Low Spinal Bone Density: A Comparative Study between Spinal Stenosis and Degenerative Spondylolisthesis

Abstract: Spinal stenosis and degenerative spondylolisthesis share many symptoms and the same treatment, but their causes remain unclear. Bone mineral density has been suggested to play a role. The aim of this study was to investigate differences in spinal bone density between spinal stenosis and degenerative spondylolisthesis patients. 81 patients older than 60 years, who underwent DXA-scanning of their lumbar spine one year after a lumbar spinal fusion procedure, were included. Radiographs were assessed for disc heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
2
15
0
5
Order By: Relevance
“…The study by Anderson et al in 2013 found a higher rate of low bone mass in patients with degenerative spondylolisthesis than spinal stenosis. 3 These patients had higher pain scores at 1 year after surgery. This highlights the importance of the treatment of osteoporosis before surgery to improve postoperative outcomes.…”
Section: Introductionmentioning
confidence: 89%
“…The study by Anderson et al in 2013 found a higher rate of low bone mass in patients with degenerative spondylolisthesis than spinal stenosis. 3 These patients had higher pain scores at 1 year after surgery. This highlights the importance of the treatment of osteoporosis before surgery to improve postoperative outcomes.…”
Section: Introductionmentioning
confidence: 89%
“…До 80 % случаев выявления дегенеративного спондилолистеза происходят на уровне L 4 -L 5 , 20 % -на L 3 -L 4 и L 5 -S 1 . Наиболее часто дегенеративный спондилолистез возникает у пациентов старше 40 лет, в 39 % случаев сопровождается остеопорозом [14].…”
Section: эпидемиологияunclassified
“…За точку отсчета в шкале Hounsfield (0 HU) принята плотность воды. Средние денситометрические показатели костной плотности составляют +400 HU и выше [14,54].…”
Section: результаты лечения и осложненияunclassified
See 1 more Smart Citation
“…Da die Erkrankung bei Frauen etwa 4× häufiger vorkommt als bei Männern, werden auch hormonelle Ursachen diskutiert. Eine verminderte Knochendichte könnte ebenfalls eine Rolle bei der Entstehung der DLS spielen [7]. Rein mechanische Konzepte sehen in einem hohen Beckenneigungswinkel (PI, Pelvic Incidence) einen Risikofaktor für die Entwicklung der degenerativen lumbalen Spondylolisthese [8].…”
unclassified